Research on Network Security Risk Assessment Method Based on Improved AHP - Li, Juan; Yan, Lina; Wang, Jingyu; Fu, Tao (Journal of physics. Conference series, 2021)
Aiming at the problem that the data cannot pass the consistency test in the analytic hierarchy process (AHP), an improved AHP is proposed. The implementation scheme of the improved AHP based on D-S evidence theory and gray theory is designed, and matlab is used for simulation experiment. The results show that the improved method can effectively enhance the reliability of network security risk assessment results.